Utilization of water hyacinth weed (Eichhornia crassipes) for the removal of Pb(II), Cd(II) and Zn(II) from aquatic environments: an adsorption isotherm study - Mahamadi, C.; Nharingo, Tichaona (2016)
The potential of Eichhornia crassipes biomass for the adsorption of three metal ions, Pb(II), Cd(II) and Zn(II), from aqueous solution was studied using five two-parameter adsorption isotherm equations – Langmuir, Freundlich, Flory-Huggins, Temkin and Redlich–Peterson isotherms. The equilibrium adsorption data were obtained at different initial metal ion concentrations (Co = 10–60 mg/L), 3 h contact time, 30 °C temperature, a dosage of 2 g/L, agitation rate of 150 rpm and buffered at pH 4.84. Langmuir isotherms gave monolayer sorption capacities (qm) of 26.32, 12.60 and 12.55 mg/g for Pb(II), Cd(II) and Zn(II) metal ions, respectively. The same trend of metal uptake was indicated by plots of sorption favourability (SF). Negative values of indicated that the adsorption was spontaneous and exothermic in nature, and values from the Temkin isotherm constant, bT, suggested a mechanism consistent with an ion-exchange process. The results from these studies indicated that E. crassipes biomass has promising potential for the removal of toxic metals from aquatic environments.